2022
DOI: 10.3390/cancers14041069
|View full text |Cite
|
Sign up to set email alerts
|

Use of Patient-Derived Organoids as a Treatment Selection Model for Colorectal Cancer: A Narrative Review

Abstract: Surgical resection is the mainstay in intended curative treatment of colorectal cancer (CRC) and may be accompanied by adjuvant chemotherapy. However, 40% of the patients experience recurrence within five years of treatment, highlighting the importance of improved, personalized treatment options. Monolayer cell cultures and murine models, which are generally used to study the biology of CRC, are associated with certain drawbacks; hence, the use of organoids has been emerging. Organoids obtained from tumors dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Patients were then treated with medication based off their organoid's sensitivity results. 68 out of 80 patients had the same response as their organoid counterpart when treatment was complete [18,20].…”
Section: Drug Therapy Testingmentioning
confidence: 87%
See 1 more Smart Citation
“…Patients were then treated with medication based off their organoid's sensitivity results. 68 out of 80 patients had the same response as their organoid counterpart when treatment was complete [18,20].…”
Section: Drug Therapy Testingmentioning
confidence: 87%
“…For patients with stages I-III colorectal cancer, the first course of treatment is resection of the tumor, followed by adjuvant chemotherapy, which usually consists of 5-Flourouracil (5-Fu) and oxaliplatin. Although this approach can be successful short-term, patients have roughly a 40% chance of disease recurrence within 5 years [18].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…On the basis of this model, many laboratories have established PDO from different tumor types to study the cancer biology and in several cases their predictive value in drug sensitivity testing aiming to their use for personalized treatment (14). In line with their original intestinal development, this has been particularly frequent in CRC (7,15). According to the 100% negative predictive value of drug assays in PDO models (16), the lack of effect of oxaliplatin suggested that this drug was not a valid therapeutic option for our patient.…”
Section: Discussionmentioning
confidence: 99%
“…They have the potential to avoid futile treatments and harmful side effects for the patients. Studies addressing the use of organoids to treat patients with CRC are emerging in the literature (7). Patients with CRC peritoneal metastases treated with HIPEC or PIPAC represent a unique subgroup of patients in which tumor specimen from the metastatic site can be sampled during the intervention in order to generate organoids and perform the drug-screening analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Assembloids exhibit an even greater level of complexity, as multiple cell types are used to recapture the multitude of tissues of which the target organ is built in vivo [60,61]. PDCO-derived organoids are investigated as potential clinical tools for the personalization of oncological treatment and response prediction [62][63][64]. The merger of 3D-bioprinting and organoid technologies both accelerates organoid formation and increases the potential organoid complexity [65].…”
Section: D-bioprinting Applications In Solid Tumor Microenvironment R...mentioning
confidence: 99%